Near-Infrared Spectroscopy for Spinal Cord Monitoring—A Roadmap to Translational Research in Aortic Medicine - von Aspern, Konstantin; Haunschild, Josephina; Garbade, Jens; Etz, Christian D. (AORTA, 2023)
Extensive aortic aneurysms represent a unique challenge necessitating interdisciplinary efforts for safe and effective treatment. Despite various adjunctive neuroprotective strategies, ischemic spinal cord injury remains a devastating complication. This article describes the implementation of collateral network near-infrared spectroscopy as the first noninvasive spinal cord monitoring modality in the setting of extensive open and endovascular aortic repair, from early conceptualization to clinical utilization. Potential capabilities and remaining uncertainties based on current evidence are outlined and discussed.
Keywords: collateral network near-infrared spectroscopy; cnNIRS; spinal cord injury; spinal cord monitoring; translational research